Application of new ZnO nanoformulation and Ag/Fe/ZnO nanocomposites as water-based nanofluids to consider in vitro cytotoxic effects against MCF-7 breast cancer cells. (17th November 2017) - Abdolmohammadi, Mohammad Hossein; Fallahian, Faranak; Fakhroueian, Zahra; Kamalian, Mozhgan; Keyhanvar, Peyman; M. Harsini, Faraz; Shafiekhani, Azizollah
Abstract: Novel formulations of nanocomposites derived from ZnO nanoparticles have provided potential biomedical applications as a new strategy for treatment of breast cancer. In this research, two types of ZnO nanomaterials were synthesized by sol–gel hydrothermal process and co-precipitation containing fast quenching and also surface modification methods. The cytotoxic effects on growth of the breast cancer cell lines MCF-7 were evaluated by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay. Cell viability of the breast cancer cell line MCF-7 was reduced with increasing ZnO nanofluid concentrations at 48 and 72 h of treatment. The IC50 value of MCF-7 cells after 72 h of treatment with the first product ZnO (a) and second one ZnO (c) were measured as 51.02 and 48.63 μg/ml, respectively ( P  < 0.05).